Expressão imuno-histoquímica da e-caderina e do CD44v6 em carcinoma epidermóide de lábio inferior e língua - Cruz, Maria Carmen Fontoura Nogueira da (2006)
The objective of this study was perform, by the streptoavidin-biotin technique, an immunohistochemical analysis of the E-cadherin and CD44v6 in 15 lower lip squamous cell carcinomas and 15 of tongue, with varied histologic gradation of malignidade, in order to establish a possible relation between the expression these proteins and the anatomical localization of the lesions, metastasis, as well as with the Bryne`s histolologic grading of malignancy system. It was not observed significant statistical association between the localization of the lesions and the malignancy score, however, had a significant correlation between the histologic parameters of malignancy gradation and the total score of malignancy, being that the parameter degree of keratinization presented the highest correlation (r = 0,844). Taking in consideration the anatomical localization of the lesions, it was not significant difference between the profile of expression and the amount of immunopositive cells for Ecaderina and CD44v6. To the metastasis variable, also it was not observed significant difference between the profile of expression and the amount of immunopositive cells for evaluated proteins. However, it was observed a statistical significant difference in relation to the scores of malignancy, being that the low score presented the highest values for the profile of expression and the amount of immunopositive cells for the E-caderina and the CD44v6. It was observed a statistically significant and negative correlation between the expression profile, the amount of E-cadherin and CD44v6 immunopositive cells and the total score of malignancy. Therefore, based in the results of this study, it was concluded that the expression of the immunohistochemical markers E-caderina and CD44v6 did not constitute histological indicator of aggressiveness for the patients with lower lip and tongue squamous cell carcinomas